Lets Vocab at STEM helps enhance pupils command of English vocabulary - Siti Sarah, Sukor (2019)
The Centre for Modern Languages & Human Science (CMLHS) at Universiti Malaysia Pahang (UMP) recently coordinated a field trip for 100 primary school pupils from around Pekan to the university to participate in a programme called "Let's Vocab @ STEM".